Discours, mémoires et contextes : à propos du fonctionnement de l’allusion dans la presse - Sophie Moirand (Corela)
French discourse analysis, which originally centered on political discourse, developed during the seventies and eighties outside the cognitive paradigm. The words "cognition" and "cognitive" seem nonetheless to have been reintroduced implicitly as soon as the question arose of theorizing the functioning of discourse, in particular behind the notions of memory and forgetting and in their implicit links with ideas of context, thought and human experience: the existence of the pre-constructed, of inter-discourse and Pêcheux's double forgetting theory, notions of transverse discourse and inter-discourse memory (Courtine and Lecomte), the idea of the word "that never forgets where it has been" and thus the discourses it has already encountered (Bakhtine) as well as the notion of collective memory (Halbwachs) point, although not explicitly, to the cognitive. This article attempts first of all to unravel what is meant by memory in discourse analysis since Courtine and Lecomte and within the present framework of a discursive semantic theory which has been renewed by the taking into account of the relations between the (social) subject and (social) reality as he perceives, interprets and categorizes it before representing it for others. We then examine, in the light of analyses carried out on a corpus from the French daily press, what words and speech bring with them (vertical threads of discourse) when they are inscribed in the materiality of discourse (horizontal thread of discourse). This will allow us to talk about the forms of memory (episodic, perceptive, procedural, semantic and working memory) which are evoked and the role of allusion in the memorization and recall, or even in the construction, of knowledge. Finally we show how the appeal to the memory of words and speech can be used by the speaker to modify the perception of a text as it unfurls, in particular in discursive configurations like media explanation of argumentation, in other words within the framework of the model elaborated by J.-B. Grize: a reasoned organization of thought content, the aim of witch is to modify the cognitive representations of those addressed.